Técnicas de análise do perfil de execução e otimização de programas em química computacional - Gomes,André S. P. (2002)
In this paper we review the basic techniques of performance analysis within the UNIX environment that are relevant in computational chemistry, with particular emphasis on the execution profile using the gprof tool. Two case studies (in ab initio and molecular dynamics calculations) are presented in order to illustrate how execution profiling can be used to effectively identify bottlenecks and to guide source code optimization. Using these profiling and optimization techniques it was possible to obtain significant speedups (of up to 30%) in both cases.